Assessment of The Eﬀectiveness of Fiscal Policy in The Context of Socio-Economic Interests - I. A. Karpukhno (Статистика и экономика, 2022)
Purpose of the study. The purpose of the study is to propose a conceptual approach to assessing the effectiveness of fiscal policy in the context of socio-economic interests based on the identification of the position of the state not only as a tax recipient, but also as a regulator of economic activity. In accordance with the goal, the following tasks are set: 1) within the framework of a conceptual approach to assessing the effectiveness of fiscal policy in the context of the socio-economic interests of the approach, to propose a mathematical interpretation of the target function of taxes paid by an economic entity - taxpayer and the target function of tax revenues to the state; 2) justify the functional limitations of these objective functions and propose a logic for justifying the parameters of the Laffer curve; 3) propose an approach to explaining the shape of the Laffer curve, due to the rotation of the parabola on the axis of penalties; 4) to confirm the proposed approach, on the basis of correlation analysis, evaluate the closeness of the relationship between the level of the tax burden, the number of on-site audits and the amount of additionally assessed funds for an on-site tax audit.Materials and methods. The article uses information from the scientific works of Russian and foreign scientists, Internet resources. The following methods were used in the work: the method of logical analysis (for the logical substantiation of the parameters of the Laffer curve); correlation analysis (to identify the relationship between the level of the tax burden, the number of on-site audits and the amount of additionally assessed funds for an on-site tax audit); the assessment of the tightness of the connection was checked according to the Chaddock scale; graphical method (to reflect different approaches to constructing the Laffer curve).Results. The paper proposes a conceptual approach to assessing the effectiveness of fiscal policy in the context of socio-economic interests, which involves highlighting the position of the state not only as a tax recipient, but also as a regulator of economic activity. Within the framework of this approach, a mathematical interpretation of the target function of taxes paid by an economic entity - a taxpayer and the target function of tax revenues to the state are proposed. The functional limitations of these objective functions are substantiated and the logic of justifying the parameters of the Laffer curve is proposed. Various approaches to the construction of the Laffer curve are considered. The arguments of critics of the Laffer curve are analyzed. An approach is proposed to explain the shape of the Laffer curve due to the rotation of the parabola on the penalty axis. The logic of substantiation of the parameters of the Laffer curve is determined. Based on the correlation analysis, the tightness of the relationship between the level of the tax burden, the number of on-site audits and the amount of additionally charged funds for an on-site tax audit was estimated. A trend towards a decrease in the number of on-site inspections (as a form of tax control) is revealed, while maintaining the main fiscal task of increasing revenues to the budget of the Russian Federation.Conclusion. The proposed conceptual approach to assessing the effectiveness of fiscal policy in the context of socio-economic interests makes it possible to separate the assessment of fiscal efficiency and macroeconomic efficiency of fiscal policy and be guided by the proposed parameters when determining tax rates, which will allow using the fiscal policy of the state as an element of harmonizing the socio-economic interests of society.